2002
DOI: 10.1002/1521-3862(20020704)8:4<163::aid-cvde163>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mononuclear Alkoxide Precursors for the MOCVD of ZrO2 and HfO2 Thin Films

Abstract: Thin films of ZrO 2 and HfO 2 have been deposited by liquid injection metal±organic (MO)CVD using a range of new alkoxide precursors, [Zr(O t Bu) 2 (mmp) 2 ] (1), [Hf(O t Bu) 2 (mmp) 2 ] (2), [Zr(mmp) 4 ] (3), and [Hf(mmp) 4 ] (4): (mmp = 1-methoxy-2-methyl-2-propanolate, OCMe 2 CH 2 OMe). The complexes are mononuclear and volatile, and are significantly less reactive to air and moisture than existing Zr and Hf alkoxide precursors such as [Zr(O t Bu) 4 ] and [Hf(O t Bu) 4 ]. The ZrO 2 and HfO 2 films were grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
71
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 33 publications
(68 reference statements)
5
71
0
Order By: Relevance
“…Analysis of literature reports exhibited that the main products of reactions between zirconium alkoxides (Zr(OR) 4 , R = i Pr, t Bu) and b-diketonates [9,14,18] or b-ketoesters [15] were bi-nuclear complexes of general formulas [Zr(O i Pr) 3 (R 0 )] 2 (R 0 = dmap (1-dimethylaminopropan-2-olate), thd (2,2,6, 6-tetramethylheptane-3,5-dionate), tbaoac (tert-butylacetoacetate)) and [Zr(O t Bu) 2 (dmae)] 2 (dmae-dimethylaminoethanolate). However, compounds mentioned above showed the relatively low volatility, the following volatile species: [Zr(O t Bu) 3 3 ], are formed during their thermal decomposition.…”
Section: Spectroscopic Characterization Of Synthesized Zr(iv) Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of literature reports exhibited that the main products of reactions between zirconium alkoxides (Zr(OR) 4 , R = i Pr, t Bu) and b-diketonates [9,14,18] or b-ketoesters [15] were bi-nuclear complexes of general formulas [Zr(O i Pr) 3 (R 0 )] 2 (R 0 = dmap (1-dimethylaminopropan-2-olate), thd (2,2,6, 6-tetramethylheptane-3,5-dionate), tbaoac (tert-butylacetoacetate)) and [Zr(O t Bu) 2 (dmae)] 2 (dmae-dimethylaminoethanolate). However, compounds mentioned above showed the relatively low volatility, the following volatile species: [Zr(O t Bu) 3 3 ], are formed during their thermal decomposition.…”
Section: Spectroscopic Characterization Of Synthesized Zr(iv) Complexesmentioning
confidence: 99%
“…Zirconium(IV) alkoxides show suitable volatility but the high reactivity of these compounds toward hydrolysis makes them difficult to handle. Moreover, the majority of these compounds are oligomeric of a low volatility, due to the tendency of zirconium(IV) ions to expand their coordination sphere to numbers 6-8 and it implies the necessity to control the reactivity of zirconium alkoxides [14]. One approach is the use of bidendate ligands, such as b-diketonates, carboxylic acids, or other, which can decrease the parent alkoxides reactivity [9,13,[15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Detailed study has demonstrated that the size of as-prepared ZnO QDs was influenced by the deposition time, ambient temperature and laser power. [101][102][103]. As nano-sized ZnO has attracted a lot of attention in the past decade, MOCVD also began to be used in fabricating ZnO nanostructures, such as nanowires, nanorods [104,105].…”
Section: Pulsed Laser Ablation (Pla or Pld)mentioning
confidence: 99%
“…Recently, new hafnium homoleptic alkoxide compounds fully saturated such as Hf(dmae) 4 (dmae = dimethylaminoethoxide) [2] and Hf(mmp) 4 (mmp = 1-methoxy-2-methyl-2-propanolate) [3] and heteroleptic complexes such as Hf(O t Bu) 2 (mmp) 2 [4] and Hf(O i Pr) 2 (tbaoac) 2 (tbaoac = tertbutylacetoacetato) [5] have been successfully used since they both inhibit oligomerization and increase the coordination number of the central metal.…”
mentioning
confidence: 99%
“…The oxygen and nitrogen atoms are approximately coplanar with the hafnium atom while the chloride ions are above and below this plane and bent toward the DME ligand. The N(1)-Hf-N(2) angle is opened up to 103.0(3)°a nd the Cl(1)-Hf-Cl (2) The catalytic activity of the complex Hf(NEt 2 ) 2 -Cl 2 (DME) was tested for the ethylene polymerization treating it with a stoichiometric amount of (NHMe 2 Ph)-B(C 6 F 5 ) 4 as activator and with Al(i-Bu) 3 (TIBA) as scavenger using a procedure already reported in the literature [17,18]. The specific reaction conditions, the catalytic activity and some properties of the polymers such as the average molecular weights (obtained by viscometry) and melting points are reported in Table 1.…”
mentioning
confidence: 99%